Dynamic Linkages between Energy Consumption, Foreign Direct Investment, and Economic Growth: A New Insight from Developing Countries in Asia - Darwin, Ranti; Sari, Dyah Wulan; Heriqbaldi, Unggul (International Journal of Energy Economics and Policy, 2022)
This study aims to determine the dynamic relationship between energy consumption, FDI, and economic growth in developing countries in the Asian Region by adding other control variables. This study uses a panel data model approach and a dynamic GMM panel with a dataset of 21 developing countries in the Asian Region from 2000-2019. The results of the panel data model report that FDI and energy consumption can significantly increase economic growth. However, poverty and interest rates can reduce economic growth. On the other hand, the dynamic GMM approach states that FDI and energy consumption can increase economic growth with a significant positive relationship. However, poverty, interest rates, and inflation have a negative and significant relationship to economic growth in developing countries in the Asian Region. In line with the study findings, these findings are of more interest to policymakers in this country. Therefore policy recommendations are made to increase the economic growth of developing countries in the Asian Region.